2016
DOI: 10.1080/09669582.2016.1158829
|View full text |Cite
|
Sign up to set email alerts
|

Greenhushing: the deliberate under communicating of sustainability practices by tourism businesses

Abstract: Greenhushing selectively communicates fewer pro-sustainability actions by businesses than are practiced; based on a perception of customers' rights to consumerism. We first studied the gap between the communication of sustainability practices in the audits and websites of 31 small rural tourism businesses in the Peak District National Park (UK). The analysis showed that businesses only communicate 30% of all the sustainability actions practiced. Their websites emphasised customer benefits, using explicit, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 57 publications
0
68
0
Order By: Relevance
“…Earlier research has shown that sustainability messages, even from sustainability award‐winning firms, are not persuasive (Villarino & Font, ). This has been deemed to stem from their lack of belief that their messages will be effective (Borden, Coles, & Shaw, ; Font, Elgammal, & Lamond, ). Recommendations for subsequent research are therefore two‐pronged: (a) to study how the degree of collectivism vs individualism affects the ATTs and approaches of staff in tourism firms to writing sustainability messages and (b) to conduct experiments manipulating sustainability messages on the basis of appealing to one's ATTs and SEBs in order to understand how staff in tourism businesses respond to the proposed new communication methods and to measure tourists' actual behaviour change and compare this with behavioural intention.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier research has shown that sustainability messages, even from sustainability award‐winning firms, are not persuasive (Villarino & Font, ). This has been deemed to stem from their lack of belief that their messages will be effective (Borden, Coles, & Shaw, ; Font, Elgammal, & Lamond, ). Recommendations for subsequent research are therefore two‐pronged: (a) to study how the degree of collectivism vs individualism affects the ATTs and approaches of staff in tourism firms to writing sustainability messages and (b) to conduct experiments manipulating sustainability messages on the basis of appealing to one's ATTs and SEBs in order to understand how staff in tourism businesses respond to the proposed new communication methods and to measure tourists' actual behaviour change and compare this with behavioural intention.…”
Section: Resultsmentioning
confidence: 99%
“…It has even been identified as the major reason tourists conduct last chance tourism [19], but tourism businesses seldom mention this concept in their daily operations [20,21]. Hence, tourism has actually become a major contributor of greenhouse gas emissions worldwide [22] despite the many forms of tourism, such as coastal tourism [23], ski tourism [24,25], and animal watching tourism [26,27] Major studies have examined the climate change that tourism brings from the perspective of tourists.…”
Section: Thematic Coveragementioning
confidence: 99%
“…The nuanced account they provide gives a candid understanding of the importance of conservation to tourism professionals' social identity as professional safari travel agents, how selecting suppliers with conservation efforts has been normalised, and yet how these choices are not verbalised as part of the sales process for fear that they will jeopardise a focus on the hedonistic benefits of a unique experience, that just happens to be sustainable. This moral muteness and customer-centred experiential understanding (Kreps & Monin, 2011;Malone et al, 2014) was elaborated in the study by Font, Elgammal and Lamond (2017) as greenhushing, that is, the deliberate underplaying of sustainability attributes in the marketing process, for fear that consumers will see the company as less competent or the product or service of lower quality. What they have in common is that they report on businesses that are not prepared to wait for the marketplace to demand sustainable products, and have found methods to take the initiative in supplying them as part of a better consumer experience Mossaz & Coghlan, 2017).…”
Section: The Product Development Approachmentioning
confidence: 99%